Islamic Banks and Its Role in Reducing Poverty - Pungky Lela Saputri; Muhammad Faisal Yul Zamrudi (Journal of Economic, Management, Accounting and Technology (JEMATech), 2023)
This study aims to analyze the effect of financing disbursed by Islamic banks on reducing the poverty rate in Indonesia. This study used timeseries data tested using multiple linear regression analysis. Sharia bank financing data was obtained from Sharia Banking Statistics by the Financial Services Authority and poverty data in Indonesia obtained from BPS was used in this study. The results showed that murabahah has an effect on reducing the poverty rate, while the greater distribution of mudharabah financing has an impact on increasing poverty, and the existence of musyarakah financing has no effect on poverty in Indonesia at all.